2009
DOI: 10.1287/msom.1080.0223
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Delay Estimation Based on Delay History

Abstract: Motivated by interest in making delay announcements to arriving customers who must wait in call centers and related service systems, we study the performance of alternative real-time delay estimators based on recent customer delay experience. The main estimators considered are: (i) the delay of the last customer to enter service (LES), (ii) the delay experienced so far by the customer at the head of the line (HOL), and (iii) the delay experienced by the customer to have arrived most recently among those who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…A second branch of research focuses exclusively on delay predictions, without considering the impact on the behavior of customers. The work of Whitt (1999b), Ibrahim and Whitt (2008, 2009a, 2009b, 2010, 2011a, 2011b, and Ibrahim, Armony, and Bassamboo (2015), as well as the present paper, fall into this category.…”
Section: Literature Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…A second branch of research focuses exclusively on delay predictions, without considering the impact on the behavior of customers. The work of Whitt (1999b), Ibrahim and Whitt (2008, 2009a, 2009b, 2010, 2011a, 2011b, and Ibrahim, Armony, and Bassamboo (2015), as well as the present paper, fall into this category.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Nakibly (2002), Armony, Shimkin, andWhitt (2009), andWhitt (2009a) propose simple heuristic predictors that return the delay times experienced by previous customers. As examples of DH-based predictors, one may return the waiting time of the last customer to enter service (LES), the customer at the head of the line (HOL), the last customer to complete service (LCS), or the most recently arrived customer to complete service (RCS).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The RRASE of QL a ranges from about 14% for s = 100 to about 4% when s = 1000. From Section 4 of Ibrahim and Whitt (2009a) and Section 5 of Ibrahim and Whitt (2009b), we have theoretical results that provide useful perspective for the more complicated models we consider here. For example, we anticipate that the ASE of QL a and HOL a should be inversely proportional to the number of servers.…”
Section: Results For the M(t)/m/s + M Modelmentioning
confidence: 99%
“…In Ibrahim and Whitt (2009a), we studied the performance of QL s and HOL in the GI/M/s queueing model, which has a renewal arrival process and no abandonment. We showed that QL s is the most effective predictor, under the MSE criterion, in the GI/M/s model.…”
Section: Previous Researchmentioning
confidence: 99%